2014
DOI: 10.1002/jrs.4529
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic characterization of CH4 density over a wide range of temperature and pressure

Abstract: The positions of the CH4 Raman ν1 symmetric stretching bands were measured in a wide range of temperature (from −180 °C to 350 °C) and density (up to 0.45 g/cm3) using high‐pressure optical cell and fused silica capillary capsule. The results show that the Raman band shift is a function of both methane density and temperature; the band shifts to lower wavenumbers as the density increases and the temperature decreases. An equation representing the observed relationship among the CH4 ν1 band position, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 19 publications
3
53
0
Order By: Relevance
“…N 2 (Figure b) shows a decrease in peak position with increasing temperature at constant density over the studied region. The density‐peak position relationship for CH 4 shown in Figure a is similar to that reported by Lin et al and Shang et al The density‐peak position relationship for CO 2 shown in Figure c is similar to that reported by Wang et al…”
Section: Resultsmentioning
confidence: 99%
“…N 2 (Figure b) shows a decrease in peak position with increasing temperature at constant density over the studied region. The density‐peak position relationship for CH 4 shown in Figure a is similar to that reported by Lin et al and Shang et al The density‐peak position relationship for CO 2 shown in Figure c is similar to that reported by Wang et al…”
Section: Resultsmentioning
confidence: 99%
“…In the CH 4 ‐bearing fluids, including pure CH 4 , CH 4 ─H 2 O, CH 4 ─N 2 , CH 4 ─C 2 H 6 , and CH 4 ─NaCl─H 2 O systems, the Raman shift (peak position) of the ʋ 1 band of CH 4 is an effective pressure (density) indicator . This is mainly because the peak position of the ʋ 1 band of CH 4 is very sensitive to pressure, and the magnitudes of its pressure‐dependent shifts are sufficiently large enough for pressure determinations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the derived uncertainties for the calculated pressures tend to be very small. The calibrated Raman shifts for cyclohexane have been applied to evaluate the effect of pressure (or density) and temperature on the Raman shifts of methane ν 1 peak positions …”
Section: Discussionmentioning
confidence: 99%
“…of Lu et al ). Because these differences are not a result due to the small difference in temperatures of these samples, therefore, calibration of each Raman spectroscopic system is needed to minimize the effects of other unknown factors on the measured Raman shifts. Also, it is absolutely necessary to use the same instrument setting and software to determine the position of Raman bands for both the sample and the calibrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation